EFFECT OF PHOSPHORUS AND SULFUR FERTILIZERS ON GROWTH AND TIELD SHALLOTS (Allium ascalonicum L.) BIMA VARIETY - Rika Mustikawati; Tadjudin Tadjudin; Alfandi Alfandi (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2020)
This study aims to determine: (1) Interaction between phosphorus and sulfur fertilizers on the growth and yield of shallots (Allium ascalonicum L.) Bima variety, (2) Dosage of phosphorus and sulfur fertilizers which have a good effect on growth and yield of shallots (Allium). ascalonicum L.) Bima variety, and (3) The relationship between growth components and yield components of shallots Bima variety. The research was carried out in a rice field area belonging to the UPTD of the Food and Agriculture Security Service in Cisantana Village, Cigugur District, Kuningan Regency, from May to July 2020. The method used in this research is an experimental method, with a randomized block design, factorial pattern, which consists of two treatment factors, namely the factor of phosphorus fertilizer and sulfur fertilizer and repeated three times. The first factor of phosphorus (P) consists of four levels of treatment, namely: p0 (0 kg P2O5/ha), p1 (36 kg P2O0/ha), p2 (54 kg P2O5/ha), and p3 (72 kg P2O5/ha). The second factor of sulfur (S) consists of three levels, namely: s1 (30 kg sulfur/ha), s2 (60 kg sulfur/ha) and s3 (90 kg sulfur/ha). The results showed that: (1) there was an interaction effect between the treatment of phosphorus and sulfur fertilizers on the weight of fresh tubers and dry bulb weight of shallots, (2) phosphorus and sulfur fertilizers independently affected plant height, number of tillers per clump, number of leaves per clumps, root volume, root shoot ratio, relative growth rate, number of tubers and tuber diameter. The dosages of phosphorus fertilizer of 54 kg P2O5/ha and 60 kg sulfur/ha gave the highest fresh tuber weight and dry tuber weight per plot. The dosages of phosphorus fertilizer 54 kg P2O5/ha and 60 kg sulfur/ha give weight of fresh tubers and dry tubers per plot of 6.53 kg and 5.24 kg, equivalent to 21.77 tons / ha and 17.47 tons/ ha, and (3) there is a significant relationship between growth components, yield components with fresh tuber weight and dry tuber weight of Bima variety onion per plot.